2005
DOI: 10.1002/cncr.20896
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrence in childhood solid tumors

Abstract: Tasmanian devil lymphoid tissues (thymus, spleen, and lymph node) from seven animals, including pouch young, juvenile, and adult devils, were investigated using histological and immunohistochemical techniques. Antibodies against the conserved intracytoplasmic portion of CD3 and CD79b (T‐ and B‐cell markers, respectively) and MHC II were used to label immune cells. The thymus from the juvenile devils and the pouch young had CD3+ cells that were primarily located in the medulla of the organ. The spleen consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 82 publications
3
26
1
Order By: Relevance
“…4 Although there have been some improvements in the outcome for children with brain tumors, 5 the prognosis for children with high grade or diffuse intrinsic pontine gliomas, relapsed medulloblastoma, and ependymoma is extremely poor. 6,7 In order to achieve the necessary delicate balance between improved treatment and avoidance of damage to the developing brain, we need a better understanding of the underlying biology of these tumors.…”
mentioning
confidence: 99%
“…4 Although there have been some improvements in the outcome for children with brain tumors, 5 the prognosis for children with high grade or diffuse intrinsic pontine gliomas, relapsed medulloblastoma, and ependymoma is extremely poor. 6,7 In order to achieve the necessary delicate balance between improved treatment and avoidance of damage to the developing brain, we need a better understanding of the underlying biology of these tumors.…”
mentioning
confidence: 99%
“…The usefulness of ongoing surveillance imaging remains controversial [9, 12, 13, 17] Chong et al [18] recently reported on the radiation exposure burden placed on survivors of various cancers. Five-year cumulative estimates of individual radiation exposures were calculated to range from 10 mSv to 642 mSv (median, 61 mSv) resulting from 690 imaging procedures.…”
Section: Roles Of Surveillance Imagingmentioning
confidence: 99%
“…They further pointed out that routine scheduled surveillance appointments failed to detect half of the relapse cases they report [12]. Similarly, Howell et al [17] reported 37 recurrences of solid tumors in a cohort of 186 pediatric patients followed for a median of almost 6 years. More than half of the recurrences were symptomatic.…”
Section: Need For Outcomes Analysis Of Surveillance Imaging Studiesmentioning
confidence: 99%
See 2 more Smart Citations